2012
DOI: 10.3842/sigma.2012.094
|View full text |Cite
|
Sign up to set email alerts
|

Minkowski Polynomials and Mutations

Abstract: Abstract. Given a Laurent polynomial f , one can form the period of f : this is a function of one complex variable that plays an important role in mirror symmetry for Fano manifolds. Mutations are a particular class of birational transformations acting on Laurent polynomials in two variables; they preserve the period and are closely connected with cluster algebras. We propose a higher-dimensional analog of mutation acting on Laurent polynomials f in n variables. In particular we give a combinatorial descriptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
219
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(221 citation statements)
references
References 22 publications
2
219
0
Order By: Relevance
“…See [KN12] for an overview of Fano polytopes. We briefly recall the notation of [ACGK12,§3]. Any choice of primitive vector w P M determines a lattice height function w : N Ñ Z which naturally extends to N Q Ñ Q.…”
Section: Mutations Of Fano Polytopesmentioning
confidence: 99%
See 1 more Smart Citation
“…See [KN12] for an overview of Fano polytopes. We briefly recall the notation of [ACGK12,§3]. Any choice of primitive vector w P M determines a lattice height function w : N Ñ Z which naturally extends to N Q Ñ Q.…”
Section: Mutations Of Fano Polytopesmentioning
confidence: 99%
“…In [ACGK12] it was also shown that mutations have a natural description as a piecewise linear transformation of the lattice M . We require the following definition.…”
Section: Mutations Of Fano Polytopesmentioning
confidence: 99%
“…where the P k are polynomials. There are 3747 Minkowski polynomials (up to monomial change of variables) but Akhtar-Coates-Galkin-Kasprzyk showed that these Laurent polynomials together generate only 165 periods [1]. That is, Minkowski polynomials fall into 165 equivalence classes where f and g are equivalent if and only if they have the same period.…”
Section: A Introductionmentioning
confidence: 99%
“…where G acts as in (1), and C × acts trivially on the first factor and by rescaling on the second factor. (3) Let F = P(E) be as in (2).…”
mentioning
confidence: 99%
“…Using this it is straightforward to check that the period condition for Proof. One can check that polygons ∆ 1 and ∆ 2 differ by (a sequence of) mutations (see, say, [ACGK12]). These mutations agree with fiberwise birational isomorphisms of toric Landau-Ginzburg models modulo change of basis in H 2 (S, Z) by the construction.…”
Section: Proposition 21 the Laurent Polynomial F Sd Is A Toric Landmentioning
confidence: 99%